(untitled) (JED (Jurnal Etika Demokrasi), 2017)
This study aims to improve the learning outcomes of Civics through the application of learning models Active Giving Question and Getting Answer on Grade V Students of Primary School Inpres Tetebatu Gowa Regency. This research is a kind of descriptive class action research that is qualitative and descriptive statistic that is quantitative. The subjects of the study were the students of Grade V A of Elementary School of Inpres Tetebatu of Gowa Regency amounting to 39 people. This research was conducted in two cycles consisting of four components namely planning, action, observation / observation, and reflection. Data collection techniques used are the provision of tests and observations. The data obtained were analyzed qualitatively and quantitatively. Result of research: (1) Student learning achievement improvement on Civic subject through Active Learning Model Giving Question and Getting Answer to Grade V student of Primary School of Inpres of Tetebatu Gowa Regency. This can be seen from the cycle I that completeness of learning only reached 72% with an average of 73.52 and then rose to 87% in cycle II with an average of 81.28. (2) Application of Active Learning Model Giving Question and Getting Answer can improve the learning result of Civics in class V A Primary School of Inpres Tetebatu Gowa Regency South Sulawesi Province. Keywords: Learning Outcomes, Giving Question and Getting Answer